Anatomical enablers and the evolution of C4 photosynthesis in grasses - HODKINSON, TREVOR (My University, 2013)
C4 photosynthesis is a series of anatomical and biochemical modifications to the typical C3 pathway that increases the productivity of plants in warm, sunny, and dry conditions. Despite its complexity, it evolved more than 62 times independently in flowering plants. However, C4 origins are absent from most plant lineages and clustered in others, suggesting that some characteristics increase C4 evolvability in certain phylogenetic groups. The C4 trait has evolved 22-24 times in grasses, and all origins occurred within the PACMAD clade, whereas the similarly sized BEP clade contains only C3 taxa. Here, multiple foliar anatomy traits of 157 species from both BEP and PACMAD clades are quantified and analyzed in a phylogenetic framework. Statistical modeling indicates that C4 evolvability strongly increases when the proportion of vascular bundle sheath (BS) tissue is higher than 15%, which results from a combination of short distance between BS and large BS cells. A reduction in the distance between BS occurred before the split of the BEP and PACMAD clades, but a decrease in BS cell size later occurred in BEP taxa. Therefore, when environmental changes promoted C4 evolution, suitable anatomy was present only in members of the PACMAD clade, explaining the clustering of C4 origins in this lineage. These results show that key alterations of foliar anatomy occurring in a C3 context and preceding the emergence of the C4 syndrome by millions of years facilitated the repeated evolution of one of the most successful physiological innovations in angiosperm history.
PUBLISHED
Keywords: C4 photosynthesis; C4 photosynthesis; Genes & Society; Smart & Sustainable Planet